Appendicular sarcoidosis mimicking acute appendicitis. (16th November 2012) - Hunjan, Tia; Chaudery, Muzzafer; Zaidi, Ahsan; Beggs, Andrew D
Abstract : Appendicular sarcoidosis is a very rare cause of acute abdominal pain, with only seven cases reported previously in the literature. A 45-year-old woman, known to have sarcoidosis, presented to the emergency department with a 1-week history of epigastric and right iliac fossa abdominal pain. At diagnostic laparoscopy, an acutely inflamed appendix was found and removed as well as an omental mass which was biopsied. Subsequent histopathological examination of the appendix demonstrated appendicular sarcoidosis without acute appendicitis and chronic inflammatory changes in the omental biopsy. The patients' symptoms completely resolved postoperatively. It is important to undertake urgent operative intervention in patients with sarcoidosis who present with right iliac fossa pain, owing to the high risk of perforation.